Comparison of Visian toric collamer lens and toric acrylic intraocular lens implantation for the treatment of myopia with astigmatism - Ammar H (Dove Medical Press, 2016)
Hatem Ammar, Mohamed Anbar, Marwa M Abdellah Department of Ophthalmology, Faculty of Medicine, Sohag University, Sohag, Egypt Purpose: To compare the efficacy and outcome of phakic toric implantable collamer lens (TICL) and refractive clear lens extraction with AcrySof Toric intraocular lens (TIOL) implantation for the treatment of myopic astigmatism.Patients and methods: This study assessed eyes with myopic astigmatism >–1 D and ≤–4 D with a spherical equivalent >10 D or <10 D if the patients were unsuitable for corneal refractive surgery. These eyes were divided into group A, in which Visian Toric ICL™ Phakic TICL was implanted, and group B, which involved clear lens extraction with implantation of an AcrySof IQ toric SN60T3-9™ IOL. The outcome and complications were evaluated.Results: This study enrolled 63 eyes of 38 patients with a follow-up period of at least 6 months. The mean postoperative spherical equivalent was –0.19±0.31 D in group A and –0.21±0.28 D in group B (P=0.69). The mean postoperative cylinder value was –0.46±0.53 D in group A and –0.32±0.41 D in group B (P=0.35). Postoperative cylinder was <1 D in 76.47% and 79.31% of eyes in groups A and B, respectively. The mean endothelial cell count was reduced by 4.32% in group A and by 5.32% in group B (P=0.003). The mean postoperative intraocular pressure increased insignificantly in group A (P=0.22) and reduced significantly in group B (P=0.004). The complication rate was 11.76% in group A and 6.90% in group B.Conclusion: Both procedures showed predictable results and good visual results. However, the loss of accommodation and risk of retinal complications in the TIOL group suggest that the use of TICL for myopic astigmatism is a better choice in younger patients. Keywords: myopic astigmatism, intraocular lens implantation, Visian toric, AcrySof toric